PRINCIPLES OF DIETOTHERAPY OF INTESTINAL COLICS IN INFANTS - A.I. Khavkin; O.N. Komarova ("Paediatrician" Publishers LLC, 2011)
Dietotherapy is the basis of intestinal colics treatment in infants who have combined and artificial feeding. The article presents results of scientific studies and characterizes differentiated approach to the administration of dietotherapy for the treatment of intestinal colics. The components of the diet are: decomposed protein, decreased concentration of lactose, structured fat and probiotic culture.Key words: infants, intestinal colics, dietotherapy, hydrolyzed protein, palmitic acid.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 133-139)